Effect of near-fault ground motion and damper characteristics on the seismic performance of chevron braced steel frames. - Dicleli, Murat
This study is aimed at comparing the seismic performance of steel chevron braced frames (CBFs) with and without fluid viscous dampers (FVDs) as a function of the characteristics of the near-fault (NF) ground motion and FVD parameters. For this purpose, comparative nonlinear time history (NLTH) analyses of single and multiple storey CBFs with and without FVDs are conducted using NF ground motions with various velocity pulse periods scaled to have small, moderate and large intensities. Additionally, NLTH analyses of single- and four-storey CBFs with FVDs are conducted to study the effect of the damping ratio and velocity exponent of the FVD on the seismic performance of the frames. The analyses results revealed that the seismic performance of the CBFs without FVDs is very poor and sensitive to the velocity pulse period and the intensity of the NF ground motion due to brace-buckling effects. Installing FVDs into the CBFs significantly improved their seismic performance by maintaining their elastic behaviour. Furthermore, FVDs with smaller velocity exponents and larger damping ratio are observed to be more effective in improving the seismic performance of the CBFs subjected to NF earthquakes. However, FVDs with damping ratios larger than 50% do not produce significant additional improvement in the seismic performance of the CBFs.
Keywords: Steel; Frame; Bracing; Damping; Seismic; Near fault